Research of Axiological Dominants in Press Release Genre based on Automatic Extraction of Key Words from Corpus - L. A. Kochetova (Tsentr nauchnykh i obrazovatelnykh proektov, 2019)
The relevance of the work is determined by the interest in the study of discursive practices by corpus linguistics methods. The subject of the analysis is the axiological dominants of a genre that are objectified by key words, extracted from the corpus by statistical methods. The authors aim to show the specificity of the value dominants of the Russian-language genre of press release based on the use of the keyword method of the corpus methodology and an algorithm developed using the programming language Python, based on the measure tf-idf, which allows to objectively identify lexical and semantic dominants that represent value meanings. The study was conducted on the material of a representative specialized corpus, that combine texts of press releases posted on the official websites of major Russian companies between 2017 and 2019. Based on the analysis of lexical choices, it is established that the texts of press releases of the companies are addressed to professional investors, as well as to a wide discursive community. It is shown that the discursive practices of energy sector companies emphasize the prospects of development, care for the environment, the importance of their activities for society in general. Companies in the manufacturing sector emphasize the achievements and highlight quality and domestic origin of products. Retail network companies are focused on utilitarian values of choice, convenience and economy.